A comparative study of death metaphors in Han and Tibetan ethnic groups. Issue 7 (9th August 2022) - He, Yu; Yin, Fang; He, Yiqing; Shen, Heyong; Ip, Kuaipeng; Zhang, Jiawei
Abstract: We compared 385 Han participants and 302 Tibetan participants' death metaphors and investigated the associations between death metaphors and death attitudes. The results show that the death metaphor "Separation from loved ones" was the most common among both groups. Both groups scored highest in the Empty death metaphor subscale. Ethnicity had a significant effect on the Empty subscale and age had a significant effect on the Sorrowful death metaphor subscale. Death metaphor is significantly positively correlated with approaching acceptance and escape acceptance attitudes to death. Our comprehensive exploration of death metaphors enables a better understanding the Chinese concept of death.